2005
DOI: 10.1177/10598405050210060401
|View full text |Cite
|
Sign up to set email alerts
|

Sports Nutrition for Young Athletes

Abstract: Nutritional needs for peak athletic performance include sufficient calorie intake, adequate hydration, and attention to timing of meals. Student athletes and their advisors often are misinformed or have misconceptions about sports nutrition. This paper identifies nutritional needs of young athletes, reviews common misconceptions, and examines the nutrition knowledge of athletes and their sources of nutrition information. Topics covered include energy, carbohydrate, protein, fat and micronutrient needs, hydrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
2
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 28 publications
1
47
2
10
Order By: Relevance
“…40,41 Além disso, como a proteína é a principal fonte de produção ácida endógena através da excreção de sulfato, essa produção aumentada pode influenciar negativamente a densidade mineral óssea, se não for balanceada com uma dieta adequada (frutas e vegetais). 42 Outra substância bastante utilizada pelos usuários de academia foi a creatina, cujo maior percentual encontrado foi de 89%. 4,15 Atualmente, a suplementação de creatina tem sido amplamente estudada, pesquisadores afirmam sua capacidade de aumentar a massa muscular 43,44 principalmente, o volume das fibras tipo II; aumentar a força 38 e a capacidade anaeróbica nos exercícios de alta intensidade.…”
Section: Suplementos Alimentares Mais Utilizados No Brasilunclassified
“…40,41 Além disso, como a proteína é a principal fonte de produção ácida endógena através da excreção de sulfato, essa produção aumentada pode influenciar negativamente a densidade mineral óssea, se não for balanceada com uma dieta adequada (frutas e vegetais). 42 Outra substância bastante utilizada pelos usuários de academia foi a creatina, cujo maior percentual encontrado foi de 89%. 4,15 Atualmente, a suplementação de creatina tem sido amplamente estudada, pesquisadores afirmam sua capacidade de aumentar a massa muscular 43,44 principalmente, o volume das fibras tipo II; aumentar a força 38 e a capacidade anaeróbica nos exercícios de alta intensidade.…”
Section: Suplementos Alimentares Mais Utilizados No Brasilunclassified
“…Awareness camps on nutrition and balanced diet will help the public to maintain a proper diet. On the other hand, some researchers have shown that most students are not familiar with healthy foods needed for their body in different conditions [9,10] and need to have nutrition education programs. The present study was conducted to understand the nutritional behaviour of the college students.…”
Section: Introductionmentioning
confidence: 99%
“…College athletes have misconception about nutrition, and have poor nutrition knowledge and attitude (Nancy, Connie, Vickery, & Mcbee, 2005;Schmalz, 1993). Also Studies show that athletes not knowledgeable enough about nutritional issues and their knowledge and attitude are in average level (Chang, 1987;Sakamaki et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Athletes may often rely on coaches for nutrition guidance in certain sports. Therefore, when coaches are misinformed about nutrition, this becomes a potential problem for athletes, as well (Cotugna, Vickery, & McBee, 2005). Nutrition training can be conveyed to the individuals through regular and wide educational programs as well as the individual training himself on his own settings (Yılmaz & Özkan, 2007).…”
Section: Introductionmentioning
confidence: 99%